Treatment patterns, symptom reduction, quality of life, and resource use associated with lubiprostone in irritable bowel syndrome constipation subtype. (3rd May 2016) - Solem, Caitlyn T.; Patel, Haridarshan; Mehta, Sonam; Mody, Reema; Macahilig, Cynthia; Gao, Xin
Abstract: Objectives Real-world patient outcomes data is scarce concerning the high disease burden of IBS-C. The aim of this study was to compare patient-reported symptom control, health-related quality of life (HRQoL), resource utilization, and treatment satisfaction of lubiprostone vs non-lubiprostone treatment for irritable bowel syndrome–constipation (IBS-C). Research design and methods An observational, retrospective US chart review and computer-assisted telephone patient survey was conducted March to August 2013 recruiting women over 18 years old with physician-confirmed IBS-C who had initiated new treatment from inadequate relief of previous treatments and who had been on the new treatment ≥3 months. Multiple IBS-C treatments were permitted. IBS-C severity, time since diagnosis, age, and race were controlled using inverse probability of treatment weighting. Weighted outcomes were compared using t -tests (continuous outcomes) and chi-squared tests (categorical outcomes). Main outcomes measures Instruments included Patient Assessment of Constipation Symptoms (PAC-SYM) and IBS quality of life (IBS-QoL). A single item assessed current treatment satisfaction. Results Of 162 patients (mean age 45.9 [SD 15.3] years old, 71% white, 61.1% with moderate IBS-C), 76 switched to lubiprostone and 86 to non-lubiprostone. Groups were similar in clinical and demographic characteristics and previous 30 day IBS-C treatment. After weighting, all PAC-SYM scores were lower for lubiprostone ( P < 0.05). All IBS-QoL subscales were higher for lubiprostone including overall, dysphoria, social reaction, sexual, and relationship scores ( P < 0.05.) More lubiprostone patients reported positive treatment satisfaction (92.3% vs 71.0%, P < 0.001). Conclusions In IBS-C patients with inadequate response to previous therapies, lubiprostone improved patient-reported symptom control, treatment satisfaction, and HRQoL. Key limitations include lack of measurement of patient-reported outcomes at treatment start and potential data gaps in chart documentation.